Integration of Asmaul Husna Values in Daily Activities at Tadika Al-Fikh Orchard, Bandar Bukit Raja, Klang Malaysia - Syahputri, Amanda; Zuliana, Zuliana (Universitas Pahlawan Tuanku Tambusai, 2025)
Religious values are a fundamental aspect in education, especially in shaping children's character. Integration of Asmaul Husna values in education is expected to instill faith, sharia, and morals from an early age. This study aims to: (1) find out how the integration of Asmaul Husna values in daily activities at Tadika Al-Fikh Orchard is carried out, and (2) analyze the impact of this integration on student behavior. This study uses a qualitative method with a field research approach. Informants in this study include the principal, teachers, and students. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses data reduction techniques, data presentation, and drawing conclusions. Data validity is obtained through triangulation of sources, techniques, and time. The results of the study indicate that the Asmaul Husna values that are taught consistently have a positive impact on student behavior. Some of the values applied in daily activities include Ar-Rahman and Ar-Rahiim (compassion), Al-Adl (justice), Al-Haliim (patience), As-Samii’ and Al-Bashiir (awareness of hearing and seeing), and Al-Afuww and Ar-Ra’uf (forgiveness and compassion). The impact of this integration includes increased emotional intelligence (EQ), social and cooperation skills, and better character development. Thus, the integration of Asmaul Husana values contributes to the formation of children’s characters who are more religious and have noble morals.